Artistic Re-Appropriation and Reconfiguration of the Medium’s Milieu - Lund, Jacob (The Nordic Journal of Aesthetics, 2014)
Drawing upon Bernard Stiegler’s and Jacques Rancière’s conceptions of medium as a milieu this article seeks to address the question of the political aspects of the aesthetic in relation to the notion of medium. Based on the analysis of this theoretical question the article interprets and discusses artistic endeavors to re-appropriate and reconfigure conservative symbolic orders and media milieus that have become dissociated in relation to works of art by Alfredo Jaar and Thomas Hirschhorn.